Laparoscopic Management of Ovarian Dermoid Cysts in Birat Medical College, Teaching Hospital - Neupane, Bhanubhakta; Karki, Gyanendra Man Singh; Dahal, Prerana; Karki, Sambhu Bahadur (Birat Journal of Health Sciences, 2018)
Introduction: Spillage of contents of the dermoid cyst during surgery may cause chemical peritonitis and spillage is more likely to occur during laparoscopic surgery for the removal of the ovarian dermoid cyst. Thorough washing of peritoneal cavity with physiological solution greatly reduces the incidence of chemical peritonitis. Objective: To study the outcome of laparoscopic treatment of ovarian dermoid cysts. Methodology: This is a hospital based cross-sectional study conducted at Birat Medical College and Teaching Hospital from 2012 April to 2016 April. All patients being operated by laparoscopy for ovarian dermoid cysts were enrolled in the study. Occurrence of spillage of dermoid contents during surgery and development of symptoms and signs of chemical peritonitis in postoperative period were main outcome measures. The collected data was entered in Microsoft Excel and analyzed by SPSS software version17. Results: Eighty nine ovarian dermoid cysts from 82 patients were managed by laparoscopy. Among 89 cysts, 54(60.76%) cysts were removed by laparoscopic cystectomy, 21(23.59%) cysts were removed by laparoscopic salpingo-ophorectomy and 14(15.73%) cysts were removed by salpingo-ophorectomy with hysterectomy. Spillage of dermoid content occurred in 50 (56.17%) cysts removal. There was no conversion to laparotomy and no case of chemical peritonitis. Conclusion: The risk of chemical peritonitis is negligible with spillage of dermoid content during laparoscopic procedure when peritoneal cavity is washed thoroughly. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 273-276